Coaxial Airflow 2D Planar Simulation of Millifluidic Plant-Based Caviar Generator - Srinophakun, Penjit; Thanapimmetha, Anusith; Chiarasumran, Nutchapon; Saisriyoot, Maythee; Chuwongbandith, Kittamet; Srinophakun, Thongchai Rohitatisha (Applied Science and Engineering Progress, 2024)
Millifluidic plant-based caviar generator was investigated. Effects of parameters; continuous phase flow rate, dispersed phase flow rate, and dispersed phase aperture diameter on the equivalent diameter, degree of spherical shape, and generation rate in a coaxial airflow alginate droplet generator were examined using a computational fluid dynamics (CFD) simulation program. A 2D planar simulation together with the volume of fluid (VOF) was applied to describe the phenomenon of droplet generation. Results showed that increasing the continuous phase flow rate yielded a decrease in equivalent diameter but an increase in droplet generation rate and an increase in the degree of spherical shape. Increasing the dispersed phase flow rate yielded a decrease in the degree of spherical shape but a significant increase in the droplet generation rate as well as a slight increase in equivalent diameter. Increasing the dispersed phase aperture diameter yielded an increase in equivalent diameter but a decrease in droplet generation rate and degree of spherical shape. Overall, the device could generate from 1,400–9,000 drops per hour with around 2.3–4.0 mm in size.